Enhancing Traditional Dental Care Practices through Modern Technologies and Medical Devices: A Systematic Review - Radhi K Alanazi, Yousef; Dughayyim Alharbi, Sattam Saad; Abdullah Ali Alsultan, Mohammed; Bandar Alharbi, Fahad Ayed; Saleh Alharbi, Omar Abdullah; Qasem Atiah, Saleem Ali (Journal of Neonatal Surgery, 2025)
New technology has dramatically influenced the practice of dentistry, ushering in more effective and conservative treatments for patients. This systematic review aimed to provide a comprehensive view of the technologies most widely used as the treatment of choice in the dental office. The goal was to identify the typical applications of state-of-the-art technologies in dentistry. By extracting relevant data from databases such as PubMed, Web of Science, and Scopus, we sought to enroll the most common cutting-edge technology utilized by dentists between 2015 and 2024. Adopting more modern technology into conventional dentistry practices can significantly enhance clinical outcomes, the satisfaction of practicing dentists, and career opportunities, ultimately leading to improved patient care and safety, instilling a sense of reassurance and optimism in the audience.